Body Mass Index, Abdominal Adiposity, and Incidence of Parkinson Disease in French Women From the E3N Cohort Study. (17th January 2023) - Portugal, Berta; Artaud, Fanny; Domenighetti, Cloé; Roze, Emmanuel; Degaey, Isabelle; Canonico, Marianne; Elbaz, Alexis
Abstract : Background and Objectives: Previous studies on the relationship between body mass index (BMI) and Parkinson disease (PD) provided inconsistent results, likely due to reverse causation explained by weight loss during the prodromal phase. We examined the association of BMI and abdominal adiposity with PD incidence using lagged analyses to address the potential for reverse causation and compared BMI trajectories in patients before diagnosis and matched controls. Methods: We used data from the E3N cohort study of French women with a 29-year follow-up (1990–2018). BMI (kg/m 2 ) was computed based on self-reported weight and height up to 11 times; up to 6 waist circumference (WC) and hip circumference measures were available. PD diagnoses were validated based on medical records and drug claim databases. Multivariable time-varying Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% CIs according to BMI categories (underweight <18.5 kg/m 2 ; normal = [18.5–25.0[ kg/m 2 ; overweight = [25.0–30.0[ kg/m 2 ; obese ≥30.0 kg/m 2 ). Exposures were lagged by 5 years in main analyses; we used longer lags (10 and 20 years) in sensitivity analyses. We examined trajectories of BMI categories within a nested case-control study using multivariable generalized estimating equations multinomial logistic models. Results: Of 96, 702 women (baseline age = 40–65 years), 1, 164 developed PD. PD incidence was lower (HR = 0.76, 95% CI = 0.59–0.98, p = 0.032) among women with obesity compared with those with normal BMI. There was a similar association in analyses using longer lag times (20 years, 598 cases, HR = 0.52, 95% CI = 0.30–0.88, p = 0.016). A similar pattern was seen for WC and waist-height ratio but not waist-hip ratio. Trajectories of BMI categories (1, 196 patients and 23, 876 controls) showed that obesity was less frequent in patients with PD before diagnosis than in controls, with a statistically significant difference 29 years before. In addition, the frequency of obesity decreased 5–10 years before diagnosis in patients. Discussion: In this large cohort of women with a long follow-up, obesity was associated with a lower hazard of PD, even when measured 20 years before diagnosis, in agreement with Mendelian randomization studies. Our analyses underscore the importance of lagged analyses to account for reverse causation. These findings warrant further investigations to understand the mechanisms underlying this inverse association.